BRD4 PROTAC degrader MZ1 exerts anticancer effects in acute myeloid leukemia by targeting c-Myc and ANP32B genes. Issue 1 (31st December 2022) - Ma, Li; Wang, Jianwei; Zhang, Yongping; Fang, Fang; Ling, Jing; Chu, Xinran; Zhang, Zimu; Tao, Yanfang; Li, Xiaolu; Tian, Yuanyuan; Li, Zhiheng; Sang, Xu; et al.
ABSTRACT: Acute myeloid leukemia (AML) is a highly cancerous and aggressive hematologic disease with elevated levels of drug resistance and relapse resulting in high mortality. Recently, bromodomains and extra-terminal (BET) protein inhibitors have been extensively researched in hematological tumors as potential anticancer agents. MZ1 is a novel BET inhibitor that mediates selective proteins degradation and suppression of tumor growth through proteolysis-targeting chimeras (PROTAC) technology. Accordingly, this study aimed to investigate the role and therapeutic potential of MZ1 in AML. In this study, we first identified that AML patients with high BRD4 expression had poor overall survival than those with low expression group. MZ1 inhibited AML cell growth and induced apoptosis and cycle arrest in vitro. MZ1 induced degradation of BRD4, BRD3 and BRD2 in AML cell strains. Additionally, MZ1 also initiated the cleavage of poly-ADP-ribose polymerase (PARP), which showed cytotoxic effects on NB4 (PML-RARa), K562 (BCR-ABL), Kasumi-1 (AML1-ETO), and MV4-11 (MLL-AF4) cell lines representing different molecular subtypes of AML. In AML mouse leukemia model, MZ1 significantly decreased leukemia cell growth and increased the mouse survival time. According to the RNA-sequencing analysis, MZ1 led to c-Myc and ANP32B genes significant downregulation in AML cell lines. Knockdown of ANP32B promoted AML cell apoptosis and inhibited cell growth. Overall, our data indicated that MZ1 had broad anti-cancer effects on AML cell lines with different molecular lesions, which might be exploited as a novel therapeutic strategy for AML patients.